Formation of Translation Competence as an Important Component of Professional Training for Linguists Majoring in “Translation and Translation Studies” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article examines certain aspects of the professional training of linguistics students majoring in “Translation and Translation Studies” within the framework of a competence-based approach, which appear to be important for the development of translation competence. The development of competencies occurs through the formation of a range of knowledge, skills, and abilities that graduates need to carry out translation activities. An analysis of the content of professional and translation competence makes it possible to identify ways to improve the effectiveness of the educational process, as well as to correlate the competencies defined by the federal state educational standard in linguistics with the competencies required in the translation services market.